1999
DOI: 10.1128/aac.43.6.1441
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin versus Ciprofloxacin for Treatment of Uncomplicated Typhoid Fever in a Randomized Trial in Egypt That Included Patients with Multidrug Resistance

Abstract: To compare clinical and bacteriological efficacies of azithromycin and ciprofloxacin for typhoid fever, 123 adults with fever and signs of uncomplicated typhoid fever were entered into a randomized trial. Cultures of blood were positive for Salmonella typhi in 59 patients and for S. paratyphi A in 3 cases; stool cultures were positive for S. typhi in 11 cases and for S. paratyphi A in 1 case. Multiple-drug resistance (MDR; resistance to ampicillin, chloramphenicol, and trimethoprim-sulfamethoxazole) was presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
49
3
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(62 citation statements)
references
References 21 publications
8
49
3
2
Order By: Relevance
“…These findings are consistent with reports in the literature of relapse rates of 5%-15% for patients treated with ceftriaxone [14,[20][21][22]. Although the sample size in the present study is small, combining these results with those of our previous trials [13,14], along with those of studies by Chinh et al [15] and Butler et al [23], nearly 200 patients with blood culture-confirmed typhoid fever have been treated with azithromycin, and no relapses have occurred. The concentration of azithromycin within cells and its secretion into the biliary tree, in conjunction with the long half-life of the drug, likely explain why relapses have not occurred when treating a principally intracellular infection such as typhoid fever [14,15].…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…These findings are consistent with reports in the literature of relapse rates of 5%-15% for patients treated with ceftriaxone [14,[20][21][22]. Although the sample size in the present study is small, combining these results with those of our previous trials [13,14], along with those of studies by Chinh et al [15] and Butler et al [23], nearly 200 patients with blood culture-confirmed typhoid fever have been treated with azithromycin, and no relapses have occurred. The concentration of azithromycin within cells and its secretion into the biliary tree, in conjunction with the long half-life of the drug, likely explain why relapses have not occurred when treating a principally intracellular infection such as typhoid fever [14,15].…”
Section: Discussionsupporting
confidence: 95%
“…Combining the results of 2 previous typhoid fever treatment trials, 69 patients with blood culture-proven typhoid fever were treated with azithromycin, and only 2 remained bacteremic 4 days after starting antibiotic therapy [13,14]. In the current study, because the duration of treatment was shortened from 7 to 5 days, the ontherapy blood samples were obtained for culture on day 3, one day sooner than treatment was ended in our previous trials [13,14]. The fact that blood samples were obtained for culture earlier in the present study is postulated to be the reason for the apparent, rather than actual, prolongation of bacteremia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Azithromycin (1000 mg/d for 1 day, then 500 mg/d for 6 days) may also be effective [70][71][72]; however, clinical failure has been described despite the high leukocyte intracellular concentrations achieved with this antibiotic [73]. Aztreonam and cefixime have had variable success rates and are not considered first-line therapy [65,[74][75][76].…”
Section: Treatmentmentioning
confidence: 99%
“…It was also effective in cases of MDR typhoid. This provides a useful alternative for the management of children with uncomplicated typhoid in developing countries , Girgis et al, 1999, Frenck et al, 2000.…”
Section: Azithromycinmentioning
confidence: 99%